(untitled) (Economic and Political Thought, 2017)
Sustainable development is one of the foundations on which the European Union is based. For more than 20 years, it has also been a primary principle of Poland’s social and economic development. It may be measured with the use of a number of indicators. The demographic issues are included in the sustainable development concept. It concerns social aspects as well as economic and environmental ones. The main objective of the paper is to discuss the issues of current demographic changes in the context of sustainable social development in Poland as well as in other EU Member States. The time perspective is set for the period from 2004 to 2014. The analysis covers 25 Member States divided into two groups (EU-10, i.e. Member States that joined the EU on 1 May 2004, including Poland; and EU-15, i.e. the so-called old EU states). The theoretical part of the paper is based on documents and literature on the discussed subject. The comparative part applies sustainable development indicators most effectively reflecting the demographic changes taking place (aging society issues) in the context of sustainable social development.